Sythesis and biological evaluation of PreQo derivatives - PAUMIER, ROMAIN (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2020)
tRNA-guanine transglycosylase (TGT) is a key enzyme involved in the posttranscriptional modification of tRNA across all kingdoms of life. In eukaryotes and eubacteria, TGT catalyses the incorporation of hypermodified nucleobase queuine into the anticodon of tRNAAsn, tRNAAsp, tRNAHis and tRNATyr. Queuine hypomodification has been reported in several types of neoplasms where queuine deficiency is correlated with histological signs of malignancy. Recent work from Southern, Kelly and Connon has shown that queuine analogues can be incorporated into tRNA by TGT to affect the development of multiple sclerosis. This project seeks to exploit the catalytic activity of TGT to selectively target queuine-deficient cancer cells by disrupting the translation process with queuine analogues. A library of queuine analogues bearing aliphatic, aromatic and electrophilic side-chains at the 2-position was synthesised via amide bond formation and assessed against human epithelial mammary cancer cell line MDA-MB-231.
APPROVED